When family businesses are best : the parallel planning process for family harmony and business success - Carlock, Randel S.; Ward, John L. (New York, United States : Palgrave Macmillan, 2010)
"This book explores how effective planning and communication helps business families around the world address growth challenges as they strive to become high performing multi-generation family enterprises"-- Provided by publisher.
Includes bibliographical references (p. 234-239) and index
BSBA
Keywords: Family-owned business enterprises -- Planning; Family-owned business enterprises -- Planning -- Case studies; Businesspeople -- Family relationships; Businesspeople -- Family relationships -- Case studies